2004
DOI: 10.1097/00002508-200403000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pain-Related Fear, Lumbar Flexion, and Dynamic EMG Among Persons With Chronic Musculoskeletal Low Back Pain

Abstract: Pain-related fear is significantly associated with reduced lumbar flexion, greater EMG in full flexion, and a smaller FRR. The relationship between pain-related fear and EMG during flexion and extension appears to be mediated by reduced lumbar flexion. These results suggest that pain-related fear is directly associated with musculoskeletal abnormalities observed among persons with chronic low back pain, as well as indirectly through limited lumbar flexion. These musculoskeletal abnormalities as well as limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(117 citation statements)
references
References 43 publications
9
108
0
Order By: Relevance
“…It is possible that fear of pain might lead to muscle activation alterations that in turn lead to the spreading of pain 22, 42, 48 . Protective movement alterations potentiated by fear might cause sustained activations of muscles, producing intramuscular ischemic reactions that might directly or indirectly increase peripheral pain afferent activity 30 .…”
Section: Psychology Of Multisite Pain 16mentioning
confidence: 99%
“…It is possible that fear of pain might lead to muscle activation alterations that in turn lead to the spreading of pain 22, 42, 48 . Protective movement alterations potentiated by fear might cause sustained activations of muscles, producing intramuscular ischemic reactions that might directly or indirectly increase peripheral pain afferent activity 30 .…”
Section: Psychology Of Multisite Pain 16mentioning
confidence: 99%
“…In many low back pain (LBP) studies there is strong evidence that those subjects with LBP exhibit an altered recruitment pattern of trunk muscles when compared with healthy subjects [15][16][17][18]. Some studies reported absence or delay of FRP during complete trunk flexion, which could be used to differentiate subjects with LBP from healthy or asymptomatic subjects [7,15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported absence or delay of FRP during complete trunk flexion, which could be used to differentiate subjects with LBP from healthy or asymptomatic subjects [7,15,[17][18][19]. In contrast to LBP, there is still a lack of evidence about the changes that occur during FRP in chronic neck pain (CNP) patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although splinting of the affected area is initially protective, over time the response may become habitual, in relation to perceived pain preserved by fear of pain, rather than nociceptive signals (Neblett, 2007). Fear of pain and associated avoidance of movements considered pain provoking has been correlated with reduced spinal range of motion (Geisser, Haig, Wallbom, & Wiggert, 2004;Thomas & France, 2007;Trost et al, 2012), associated with prolonged disability (Linton et al, 2000), and has even been implicated in maladaptive patterns of motor control as back pain develops (Dankaerts & O"Sullivan, 2011;Trost et al, 2012).…”
Section: Biopsychosocial Modelmentioning
confidence: 99%
“…This ratio is significantly associated with disability, pain related fear and clinical status. It is also the only ratio sensitive to self-reported pain intensity, which has been poorly associated with FR changes in the past (Geisser et al, 2004;Neblett, Alschuler, et al, 2009). …”
Section: Quantifying Flexion Relaxationmentioning
confidence: 99%